Analysis of Business Licensing Management Through Online Single Submission Risk Based Approach for Limited Liability Companies - Amar, Muhamad; Santoso, Aris Prio Agus; Suryadi, Agung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In managing risk-based permits in Indonesia, there is a gap between das sollen (PP Number 5 of 2021 is the basis for carrying out Risk-Based business licensing) and das sein (the phenomenon of PTs which are often hampered in processing OSS RBA permits). This research aims to find out the regulations regarding processing business licensing through a risk-based online single submission risk based approach (OSS-RBA), analysis of Limited Liability Companies having difficulty in managing risk-based electronically integrated business licensing and efforts to resolve the problem of Limited Liability Companies making it difficult to process risk-based electronically integrated business licensing. This research is a type of normative juridical research that relies on primary legal materials (legislation) and secondary legal materials (literature studies). The results of this research: Regulations regarding the management of business permits through OSS-RBA are regulated in Government Regulation Number 5 of 2021 concerning Risk-Based Business Licensing. Analysis of limited liability companies having difficulty in processing risk-based electronically integrated business permits is due to overlapping regulations and the absence of implementing regulations for implementing OSS RBA in the regions. Efforts to resolve the problem of limited liability companies which are difficult to obtain risk-based electronically integrated business permits, there are two, namely 1) the government must guarantee compliance with Law Number 40 of 2007 concerning Limited Liability Companies in conjunction with Law Number 11 of 2020 concerning Copyright in conjunction with PP No. 8 in 2021 based on the provisions of the statutory hierarchy and 2) the government must make a policy so that regulations implementing the RBA OSS are made in various regions.